2020
DOI: 10.1002/ncp.10482
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia as a Predictor of Survival Among Patients With Organ Metastatic Cervical Cancer

Abstract: Background: This study was conducted to investigate the prognostic significance of sarcopenia in patients with organ metastatic cervical cancer. Methods: Accordingly, the data of 40 patients with organ metastatic cervical cancer treated at our institute from December 2004 to December 2017 were retrospectively analyzed. The correlation between clinicopathological characteristics and survival was then evaluated using univariate and multivariate analyses. Psoas muscle index (PMI), calculated from the psoas muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…In contrast, studies conducted in cervical cancer have reported inconsistent results. Yoshikawa et al measured L3 psoas muscle index (PMI) of Japanese patients with metastatic cervical cancer (n = 40) and identified L3 PMI ≤3.72 cm 2 /m 2 as an independent poor prognostic factor for OS (16). In contrast, Lee et al (17) and Matsuoka et al (18) observed no association between baseline sarcopenia and survival in patients with locally advanced cervical cancer who underwent primary CCRT or RT, similar to our results.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In contrast, studies conducted in cervical cancer have reported inconsistent results. Yoshikawa et al measured L3 psoas muscle index (PMI) of Japanese patients with metastatic cervical cancer (n = 40) and identified L3 PMI ≤3.72 cm 2 /m 2 as an independent poor prognostic factor for OS (16). In contrast, Lee et al (17) and Matsuoka et al (18) observed no association between baseline sarcopenia and survival in patients with locally advanced cervical cancer who underwent primary CCRT or RT, similar to our results.…”
Section: Discussionsupporting
confidence: 87%
“…Sarcopenia, characterized by the loss of skeletal muscle mass and function, recently emerged in the cancer research field, as it was associated with higher recurrence and mortality rates, surgical complications, and treatment-related toxicity (12)(13)(14)(15). In cervical cancer, only few studies have investigated prognostic role of pre-treatment sarcopenia, resulting in conflicting results (16)(17)(18). Moreover, all these previous studies included patients who underwent primary concurrent chemoradiation therapy (CCRT) or radiation therapy (RT), rather than primary RH.…”
Section: Introductionmentioning
confidence: 99%
“…[186], [187] Cervical Decreased psoas muscle mass (L3) is associated with decreased survival in metastatic cervical cancer. [188] The roles of VAT and SAT remain unstudied.…”
Section: Ovarianmentioning
confidence: 99%
“…Even the studies of the same institution are trying to apply different criteria. 11,12,21 It is worth noting that many studies 20,26,31 have applied skeletal muscle prognostic indexes, such as PMI and TPA, which are simpler than SMI. These diagnostic criteria have good performance in predicting the death outcome of patients, but it cannot be ignored that they have no good correlation with systemic muscle composition.…”
Section: Discussionmentioning
confidence: 99%